Antimony (Sb)-Doped Bi2s3 Nanorod Films for Photoelectrochemical Water Splitting - Radhalayam, D (Academic Press, 2025)
Bi2S3 is a promising material for photoelectrochemical (PEC) water splitting due to its favorable optoelectronic properties, abundance of non-toxic elements, and chemical stability. However, pure Bi2S3 exhibits low photocurrent efficiency due to charge recombination and slow charge transport. To enhance its performance, we doped antimony (Sb) into the Bi2S3 matrix, improving both its physical and PEC characteristics. The Sb doping concentration was varied from 0 to 3.1 at.% in Bi2S3 films, which were fabricated through chemical bath deposition followed by annealing. Undoped Bi2S3 formed nanorods with a direct bandgap of 1.26 eV and achieved a photocurrent density of 4.5 mA/cm2 at 1.0 V vs Ag/AgCl. Sb doping at 0.9 at.% increased both crystallite size and nanorod density, resulting in a bandgap of 1.43 eV and a photocurrent density of 7.0 mA/cm2. At higher Sb concentrations (2.2 to 3.1 at.%), the nanorod size further increased, while the bandgap decreased to 1.20 eV, with a corresponding increase in photocurrent density to 8.6 mA/cm2. These results demonstrate that Sb doping significantly enhances the nanorod density, photocurrent, and stability of Bi2S3 photoelectrodes. © 2024 Elsevier Inc.